Implementation of Artificial Neural Networks on Field-Programmable Gate Arrays - Salim Adrees; Ala Abdulrazeg; Wafa Shuaieb (AlQalam Journal of Medical and Applied Sciences, 2024)
Implementing Artificial Neural Networks (ANNs) on Field-Programmable Gate Arrays (FPGAs) provides a promising solution for achieving high-performance, low-latency, and energy-efficient computations in complex tasks. This paper investigates the methodology for mapping ANNs onto FPGAs, focusing on critical aspects such as architecture selection, hardware design, and optimization techniques. By harnessing the parallel processing capabilities and reconfigurability of FPGAs, neural network computations are significantly accelerated, making them ideal for real-time applications like image processing and embedded systems. The implementation process addresses key considerations, including fixed-point arithmetic, memory management, and dataflow optimization, while employing advanced techniques such as pipelining, quantization, and pruning. The research compares the accuracy and performance speedup of ANNs on CPUs versus FPGAs, revealing that FPGA-based simulations are 4680 times faster than CPU-based simulations using MATLAB, without compromising prediction accuracy. يوفر تطبيق الشبكات العصبية الاصطناعية على مصفوفات البوابات القابلة للبرمجة ميدانيًا حلاً واعدًا لتحقيق عمليات حسابية عالية الأداء و زمن أقل وكفاءة في استخدام الطاقة في المهام المعقدة. يتحقق هذا البحث من منهجية تطبيق الشبكات العصبية الاصطناعية على مصفوفات البوابات القابلة للبرمجة ميدانيًا، مع التركيز على الجوانب الحرجة مثل اختيار ألية التصميم وتصميم الدائرة الإلكترونية وتقنيات التحسين. من خلال الاستفادة من قدرات المعالجة المتوازية وإعادة برمجة مصفوفات البوابات القابلة للبرمجة ميدانيًا، يتم تسريع عمليات حساب الشبكة العصبية بشكل كبير، مما يجعلها مثالية للتطبيقات التي تتطلب الاستجابة اللحظية مثل معالجة الصور والأنظمة المضمنة. عملية التنفيذ تشمل بعض المفاهيم الاساسية، بما في ذلك حساب الاعداد الكسرية، وإدارة الذاكرة، وتحسين تدفق البيانات، مع استخدام تقنيات متقدمة مثل تنفيذ اكثر من عملية في وقت واحد وتقليل الوحدات الالكترونية المستخدمة. يقارن البحث بين دقة وسرعة أداء خوارزمية الشبكات العصبية الاصطناعية على وحدات المعالجة المركزية مقابل وحدات مصفوفات البوابات القابلة للبرمجة ميدانيًا ، حيث وجد أن تطبيق الخوارزمية على مصفوفات البوابات القابلة للبرمجة ميدانيًا أسرع بمقدار 4680 مرة من تطبيق الخوارزمية على وحدة المعالجة المركزية باستخدام MATLAB ، مع المحافظة على دقة المخرجات